Pengaruh Aksesbilitas, Fasilitas dan Viral Marketing Terhadap E-WOM dan Kepuasan Wisatawan Berkunjung di Holeo Golf and Museum - Hariati, Celine (Catalist Indo Publisher, 2025)
Tourism is a strategic sector in supporting economic growth and community welfare. Holeo Golf & Museum, a unique destination in Jakarta, combines the concepts of mini golf and a dessert museum, attracting the attention of tourists, especially the younger generation. This study aims to analyze the influence of accessibility, facilities, and viral marketing on electronic word of mouth (E-WOM) and tourist satisfaction. A quantitative approach was used with accidental sampling techniques on 150 respondents who visited Holeo Golf & Museum in January–February 2024. Data were analyzed using Structural Equation Modeling with the assistance of SmartPLS 3.0 software. The results showed that accessibility significantly influenced E-WOM but not tourist satisfaction. Facilities and viral marketing have a significant influence on E-WOM and tourist satisfaction. However, E-WOM does not significantly influence tourist satisfaction. These findings emphasize the importance of facilities and digital marketing strategies in creating positive experiences and tourist loyalty. This study recommends that tourism destination managers improve facility quality and strategically utilize social media to encourage positive reviews and enhance visitor satisfaction.